PENGARUH PEMBERIAN DETRITUS DARI BAHAN ORGANIK BERUPA LIMBAH HEWAN SEBAGAI PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP TERIPANG PASIR (HOLOTHURIA SCABRA) YANG DIPELIHARA DENGAN SISTEM KURUNGAN - Karel K. Dangmeka; Nikodemus Dahoklory; Priyo Santoso (Jurnal Akuatik, 2018)
Abstract - Sea Cucumber is one of sea water cultivation commodity which have high selling price. This study aims to determine the relative growth and growth of sand cucumber life (Holothuria scabra) by using organic matter in the form of animal waste as feed. This research has been conducted for 9 weeks from 25 May to 30 July 2017 located in Hansisi waters, Semau Island, Kupang regency. Sea cucumbers (Holothuria scabra) (20-30 g) are kept in confinement with size (1m x 50cm x 1m, 10 individuals cage). his research used experimental method by using Randomized Block Design (RAL) with 3 treatment 3 replication that is treatment A as control, treatment B giving organic material from cow waste with 10 kg dose, C treatment of organic material from goat waste with dosage 10 kg, D treatment of organic matter from chicken waste with dose of 10 kg. The results showed that giving organic material from animal waste as a feed for sand cucumber (Holothuria scabra) did not significantly affect the survival of sand cucumber (Holothuria scabra), but it had a significant effect on relative growth. The average relative growth is: treatment A as control of 30.89 g, treatment B of 75.76 g, treatment C of 164.42 g, and treatment D of 58.77 g. The highest survival was on treatment A as a control of 100%, B treatment was 100%, C treatment was 100%, and the lowest was D treatment 96,66%.Keywords: Sea Cucumber, Detritus, Animal Waste, Relative Growth, Life Cycle